A randomized, cross‐over trial of metoprolol succinate formulations to evaluate PK and PD end points for therapeutic equivalence. Issue 7 (21st May 2022) - Mosley, Scott A.; Kim, Sarah; El Rouby, Nihal; Lingineni, Karthik; Esteban, Valvanera Vozmediano; Gong, Yan; Chen, Yiqing; Estores, David; Feng, Kairui; Kim, Hyewon; Kinjo, Minori; Langaee, Taimour; et al.
Abstract: There are limited comparison data throughout the dosing interval for generic versus brand metoprolol extended‐release (ER) tablets. We compared the pharmacokinetics (PKs) and pharmacodynamics of brand name versus two generic formulations (drugs 1 and 2) of metoprolol ER tablets with different time to maximum concentration ( T max ) in adults with hypertension. Participants were randomized to equal drug doses (50–150 mg/day) administered in one of two sequences (brand‐drug1‐brand‐drug2 or brand‐drug2‐brand‐drug1) and completed 24‐h PK, digital heart rate (HR), ambulatory blood pressure (BP), and HR studies after taking each formulation for greater than or equal to 7 days. Metoprolol concentrations were determined by liquid chromatography tandem mass spectrometry, with noncompartmental analysis performed to obtain PK parameters in Phoenix WinNonlin. Heart rate variability (HRV) low‐to‐high frequency ratio was determined per quartile over the 24‐h period. Thirty‐six participants completed studies with the brand name and at least one generic product. Among 30 participants on the 50 mg dose, the primary PK end points of area under the concentration‐time curve and C max were similar between products; T max was 6.1 ± 3.6 for the brand versus 3.5 ± 4.9 for drug 1 ( p = 0.019) and 9.6 ± 3.2 for drug 2 ( p < 0.001). Among all 36 participants, 24‐h BPs and HRs were similar between products. Mean 24‐h HRV low‐to‐high ratio was also similar for drug 1 (2.04 ± 1.35), drug 2 (1.86 ± 1.35), and brand (2.04 ± 1.77), but was more sustained over time for the brand versus drug 1 (drug × quartile interaction p = 0.017). Differences in T max between metoprolol ER products following repeated doses may have implications for drug effects on autonomic balance over the dosing interval.